Policy integration: placing the spatial dimension in the health agenda. Evidence from Portugal. Issue 2 (3rd May 2016) - Santinha, Gonçalo
Abstract : The significance of spatial policies for health and well-being is well recorded. While there has been an increasing body of literature illustrating the importance of including a territorial perspective in health decision-making processes, evidence shows that policy integration between spatial and health policies is still scarce. This paper aims to develop a deeper understanding of how this integration can be considered in conceptual terms and how it is actually embraced in practice by health decision-makers. Drawing upon the concept of territorial cohesion, the paper presents and discusses the results of a research held in Portugal aiming to understand this topic.